Validity, Reproducibility, and Minimal Detectable Difference of the Functional Upper Extremity Function Test - Simplified Version - for Adults With Moderate to Severe Asthma and COPD. - Soares Correia, Natielly; Mara de Oliveira, Joice; Rugila Fernandes, Diery; Idelmar Feitosa, Denner; Martins Pereira, Daniel; Pereira do Amaral, Daniel; Mesquita, Rafael; Pitta, Fabio; Dal Corso, Simone; Couto Furlanetto, Karina (Respiratory Care, 2023)
BACKGROUND: Upper-limbs (ULs) functional tests which are valid and reliable for individuals with chronic respiratory disease (CRD) are scarce. The aim of this study was to investigate the intra-rater reproducibility, validity, minimal detectable difference (MDD), and learning effect of the Upper Extremity Function Test - simplified version (UEFT_S) functional test and to characterize its performance for adults with moderate-severe asthma and COPD. METHODS: The UEFT_S was performed twice, and the number of elbow flexions in 20 s was the outcome. In addition, spirometry, 6-min walk test (6MWT), handgrip dynamometry (HGD), and usual and maximum timed-up-and-go tests (TUG_usual and TUG_max) were also performed. RESULTS: Eighty-four individuals with moderate-severe CRD and 84 control individuals matched by anthropometric data were analyzed. Individuals with CRD presented better performance in the UEFT_S than controls (P 5 .023). UEFT_S correlated significantly with HGD, TUG_usual, TUG_max, and 6MWT (P < .047 for all). The test-retest intraclass correlation coefficient was 0.91 [0.86--0.94], and the MDD was 0.4%. CONCLUSIONS: The UEFT_S is a valid and reproducible tool to assess the functionality of the ULs in people with moderate-severe asthma and COPD. When applied in the modified form, the test can be considered simple, fast, and inexpensive, with an easy outcome to interpret.